기업시민 경영을 위한 자회사형 장애인표준사업장에 관한 연구: 포스코휴먼스 사례를 중심으로 - 정정희(Jung-Hee Jung) (인문사회과학연구, 2021)
· 연구 주제: 본 연구의 주제는 기업시민 경영을 기반으로 한 기업의 사회적 책임에 대한 필요성을 자회사형 장애인표준사업장의 사례를 통하여 살펴봄으로써 건강한 기업시민 이념을 정립시키는 것이다. · 연구 배경: 본 연구 배경은 기업은 생태적으로 그 시대정신과 사회공동체적 요구의 변화에 적응해야 중장기적으로 생존할 수 있다· 선행연구와의 차이점: 대기업이 설립한 자회사형 장애인표준사업장과 기업이념의 관련성을 연구한 선행연구는 미비했다. 본 연구는 기업의 경영 이념인 기업시민과 실현의 장으로 자회사형 장애인표준사업장의 의의와 발전방안에 대해 처음으로 논의하였음에 그 의의가 있다. 아울러 기업의 건강한 사회적 책임과 역할 및 기업시민의 개념에 주목하였으며, 기업의 사회적 책임과 기업시민의 목적과 취지에 접근하기 위해 한국 기업인들의 기업시민성 인식과 의미, 기업 경영의 투명성, 기업 문화와 윤리경영․공동체 사회와 동반 성장․장애인 관련하여 헌법의 인간 존엄성과 평등성, 국가보호 등 헌법적 관점에서 기업시민 책임의 중요성을 강조함으로서 기존의 국내·외 선행 논문과 차별화하였다. · 연구 방법: 본 연구는 기업시민에 관한 국내·외 선행연구 자료를 바탕으로 포스코휴먼스의 실천적 기업의 시대정신과 시민사회의 발전에 따른 시민정신을 인지하고 그에 따른 경제·사회적 요구는 공유경제, 포용경제 및 공정경쟁, 불균형/불평등 사회를 완화·해소할, 이 시대적 요청에 부응하고 선도적인, 모범기업을 소개하고 향후 기업시민이 나아갈 방향을 제시하면서 그 방안 마련의 필요성을 제언하였다. · 연구 결과: 본 연구의 결과물은 먼저, 포스코휴먼스의 자회사형 장애인표준사업장 운영 사례 분석을 통해 기업 현장의 연수교육 목적으로 ‘기업시민’ 개념 정의 및 필요성을 도출한다. 그 연장선에서 기업시민의 가치 창출 및 시민사회 교육의 담론으로 담아내기 위한 공동체 시민사회 요구와 기업시민이 나아갈 정책적 요구를 모토로 상생 교육을 통해 향후 기업의 성장 동력에 길라잡이 역할 수행의 이정표를 제시할 수 있을 것이다. · 공헌점 및 기대 효과: (1) 학문적 기대 효과; 기존의 기업시민에 관한 국내·외 선행연구 자료를 바탕으로 하면서도 포스코휴먼스의 실천적 기업의 시대정신과 시민사회의 발전에 따른 시민정신을 인지하고 그에 따른 경제·사회적 요구는 공유경제와 포용경제 및 공정경쟁, 불균형/불평등 사회를 완화·해소할, 이 시대적 요청에 부응하고 선도적인 모범 기업을 소개하고 향후 기업시민이 나아갈 방향을 제시 및 그 방안 마련의 필요성을 제언하였다. (2) 실천적 기대 효과; 먼저 기업 입장에서 인식하는 ‘기업시민 –기업시민성’의 개념과 중요한 특징, 특히 현대 기업문화에서의 그 중요성, 유용성, 목적을 찾기 위한 탐색적 연구를 바탕으로, 포스코의 신경영이념인 기업시민의 개념과 전개 과정 및 실천 사례를 자회사형 장애인표준사업장의 운영사례를 통해 탐색한 결과를 기술하였다. 나아가, 기업시민의 실천적 동향을 파악함과 동시에 향후 기업시민에 관한 입법 제안의 초석을 다지는 선도적 역할을 기대하고자 한다. · Research topic: The subject of this study is to summarize the healthy corporate citizenship ideology by examining the necessity of corporate social responsibility based on corporate citizenship management through the case of subsidiary-type standard workplaces for the disabled. · Research Background: The background of this study is that companies can survive in the mid- to long-term only when they adapt to changes in the spirit of the times and social community needs · Differences from prior research: Previous studies that studied the relationship between subsidiary-type standard workplaces established by large companies and corporate ideology were insufficient. This study is meaningful in that it was the first to discuss the significance and development plan of subsidiary-type standard workplaces as a venue for realization with corporate citizens, which is a corporate management ideology. In addition, it focused on corporate healthy social responsibility, role, and concept of corporate citizenship, and differentiated itself from the existing domestic and foreign papers by emphasizing the importance of corporate citizenship awareness and meaning, corporate culture, ethical management, community growth, and disability. · Research Method: Based on domestic and foreign prior research data on corporate citizens, POSCOHUMANS recognized the spirit of the times and civil society's development, and suggested the need to prepare measures by introducing leading model companies in response to this era's requests. · Research results: The results of this study first derive the definition and necessity of the concept of 'corporate citizens' for the purpose of training education at the corporate site through case analysis of the operation of a subsidiary-type standard workplace of POSCOHUMANS. As an extension of that, win-win education under the motto of community civil society demands and policy demands for corporate citizens to create value and capture civil society education as a discourse can be presented as a guide to corporate growth engines in the future. · Contribution points and expected effects: (1) Academic expected effects: Based on previous domestic and foreign research data on corporate citizens, POSCOHUMANS recognized the spirit of the times and citizenship resulting from the development of civil society, and its economic and social demands met and resolved this era's requests, suggesting directions and measures. (2) Practical expected effect: Based on exploratory research to find the importance, usefulness, and purpose of "corporate citizenship-corporate citizenship" recognized from a corporate standpoint, POSCO's neuropsychological ideology, the development process, and practice case were described. Furthermore, while grasping the practical trends of corporate citizens, we hope to play a leading role in laying the foundation for future legislative proposals on corporate citizens. KCI Citation Count: 3